Studi In Vitro Perbedaan Pelarut Pada Membran Selulosa Tandan Kosong Kelapa Sawit (TKKS) Terhadap Penurunan Kreatinin - Jayanti, Tri Dewi; Hidayah, Nur; Darsono, Putri Vidiasari; Alawiyah, Tuti (LPPM Universitas Sari Mulia, 2025)
Background: Technology membrane the more develop be one application important in field biomedicine that is dialysis in the hemodialysis process. Instrument dialysis use membrane fiber hollow made of from polymer synthesis so that the price is expensive and in Indonesia the technology This Still left behind Far. Therefore That need alternative in availability membrane as material making membrane. One of them utilise cellulose from TKKS waste.Objective: To determine the effectiveness of solvent variations in TKKS cellulose membranes in reducing creatinine levels in vitro.Methods: Cross sectional analytical observation. Quantitative testing uses Uv-Vis Spectrophotometry.Results: Membranes with a variety of solvents can reduce creatinine levels, i.e membrane more DMAc solvent effective lower rate creatinine at each cycle with rate initial 3 mg/dL, time every cycle 3 minutes 55 seconds. DMAc membrane capable lower rate every cycle namely 0,509 mg/dL, 0,486 mg/dL, 0,476 mg/dL, and 0,463 mg/dL.Conclusion: Membrane TKKS uses cellulose more DMAc solvent effective in lower rate creatinine. So that need done study more carry on in its application in the health sector.